Evaluating the impact of off-hour deliveries: An application of the TRansport Agent-BAsed model. (July 2018) - Mommens, K.; Lebeau, P.; Verlinde, S.; van Lier, T.; Macharis, C.
Highlights: Distribution where deliveries are forbidden during the night affects sustainability. Shifting deliveries to the night can improve the sustainability of logistics. A maximum of one delivery allowed per night shows the best global performance. Abstract: The expected growth of freight transport should affect the performances of our transport system if we keep with the business as usual. Especially urban settings suffer from congestion and air pollution. Shifting deliveries to the night is considered as one promising solution to alleviate the growing congestion and emissions generated by freight transport. In order to check the compatibility of night deliveries with its local environment, research has been mostly focused on the analysis of trials and on the impacts it has at a micro level. This paper aims at analysing the impact of night distribution at a macro level. It evaluates the contribution of off hour deliveries on the performances of the transport system. The paper will use TRABAM, a freight transport agent based model, to simulate the impact of different use of night distribution in supermarkets. The organisation of the freight flows resulting from the new time constraints is then evaluated according the externalities generated by these flows. The analysis shows that a distribution where deliveries are possible only during the day performs the worst since it generates the highest external costs. The business as usual gives already some good performances since night distribution is already used by some supermarkets in Wallonia. But the scenario where a maximum of one delivery per night is allowed to supermarkets is found to be the best trade-off between the benefits and drawbacks of night distribution.